A comparative study to assess drinking expectancy and functioning in alcohol dependent patients with and without co-morbid depression - Mani, Anu Mary; Srinivasan, K.; Sreedaran, Priya (International Journal of Research in Medical Sciences, 2020)
Background: Alcohol dependence syndrome (ADS) and major depressive disorder are highly prevalent. Much less is known about the expectancy of alcohol use in depressed patients with ADS. Few studies had compared the expectancy of alcohol use in ADS patients with and without co-morbid depression. Assessing the above factors may help to formulate effective prevention strategies. This study was designed to assess the difference in expectancy of alcohol use and functioning in patients with ADS with and without co-morbid depression. Methods: The difference in expectancy of alcohol use in 96 alcohol dependent patients, of which 24 had co-morbid depression and 72 without co-morbid depression was studied using drinking expectancy questionnaire. In addition, we compared the difference in functioning between the two groups using GAF. Results: Prevalence of depression in alcohol dependent patients was 25%. ADS patients with co-morbid depression had less expectancy about alcohol use for sexual enhancement and had lower level of functioning compared to ADS patients without depression. Conclusions: Less expectancy on sexual enhancement in patients with ADS and co-morbid depression could be possibly due to reduced libido in depressed patients. The observed lower functioning in ADS patients with co-morbid depression despite no difference in severity of alcohol use may be possibly explained by the added burden of both the diseases.